2018
DOI: 10.3758/s13414-018-1582-z
|View full text |Cite
|
Sign up to set email alerts
|

A kinematic examination of dual-route processing for action imitation

Abstract: The dual-route model of imitation suggests that meaningful and meaningless actions are processed through either an indirect or a direct route, respectively. Evidence indicates that the direct route is more cognitively demanding since it relies on mapping visuospatial properties of the observed action on to a performed one. These cognitive demands might negatively influence reaction time and accuracy for actions performed following a meaningless action under time constraints. However, how meaningful and meaning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 41 publications
1
9
0
Order By: Relevance
“…Within each session, a single brain region was stimulated, and participants took part in both meaningful and meaningless action imitation tasks. Since there is evidence to suggest that performing novel and known actions in a sequence could recruit a single processing route, while presenting them separately recruits separate routes ([ 61 ], but see [ 62 ], and [ 63 ]), meaningful and meaningless action trials were split into separate blocks. Task order was counterbalanced across stimulation sites.…”
Section: Methodsmentioning
confidence: 99%
“…Within each session, a single brain region was stimulated, and participants took part in both meaningful and meaningless action imitation tasks. Since there is evidence to suggest that performing novel and known actions in a sequence could recruit a single processing route, while presenting them separately recruits separate routes ([ 61 ], but see [ 62 ], and [ 63 ]), meaningful and meaningless action trials were split into separate blocks. Task order was counterbalanced across stimulation sites.…”
Section: Methodsmentioning
confidence: 99%
“…In a previous experiment (Reader et al 2018a ), in which we motion-tracked participants’ wrist movements during meaningless and emblematic meaningful gesture imitation, we observed that the imitation of meaningless gestures was associated with a longer correction period than the imitation of meaningful gestures. That is, the deceleration phase of their wrist movements was longer, as reflected by a relatively earlier time to peak velocity (TPV/MT) and time to peak deceleration (TPD/MT), despite a longer overall movement time (MT).…”
Section: Introductionmentioning
confidence: 68%
“…The block order was counterbalanced across sessions and participants. Meaningless and meaningful actions were presented in separate blocks, since there is some evidence to suggest that performing novel and known actions in a sequence recruits a single processing route, whilst presenting them separately recruits separate routes (Tessari and Cubelli 2014 ; Tessari and Rumiati 2004 , but see; Press and Heyes 2008 ; Reader et al 2018a ). Hand and finger gestures were pseudorandomly interleaved within each separate block of action meaning.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous experiment (Reader et al, 2018a), in which we motion-tracked participants' wrist 52 movements during meaningless and emblematic meaningful gesture imitation, we observed that the imitation 53 of meaningless gestures was associated with a longer correction period than the imitation of meaningful 54 gestures. That is, the deceleration phase of their wrist movements was longer, as reflected by a relatively …”
mentioning
confidence: 99%